Fashion design: Teaching and Interaction regimes (Revista de Ensino em Artes, Moda e Design, 2021)
This article focuses on the interaction regimes in the disciplines aimed at visual, verb-visual and audiovisual productions in the Fashion Design course at Centro Universitário Senac - Santo Amaro. It investigates how accident and adjustment interaction regimes can contribute to teaching. When entering the field of education, we are guided towards a constructivist orientation, which promotes the approximation of contents to the students' realities and, critical and rupture positions. For that, we resort to concepts such as: presence, identity / otherness, existence, chance, potentiality. The reflections are based on the discursive semiotics developed by Algirdas Julien Greimas and unfolded by Eric Landowski and Ana Claudia Mei Alves de Oliveira and, in the educators Paulo Freire and Fayga Ostrower. The investigation points out: the interaction regimes that occur in the teaching of the proposed cut, can be extended to other disciplines and courses; Constructivist teaching promotes the emergence of innovative works, while authoritarian teaching favors the copying of works, being linked to tradition; the need for teachers to combine the intelligible and the sensitive so that teaching and learning can be meaningful.
Keywords: Teaching; Fashion; Interaction regimes